Assessment of c-reactive protein level in oral submucous fibrosis and oral squamous cell carcinoma patient - Geeta Sharma; Randhir Kumar; Sharib Abdus Salam; Prashant Bhasin; Nishant Kumar Tewari; Suman Yadav (Wolters Kluwer Medknow Publications, 2021)
Background: Potentially malignant disorders are highly prevalent in India. In this study, we assessed C-reactive protein (CRP) levels in patients with oral submucous fibrosis (OSMF) and oral squamous cell carcinoma (OSCC). Methodology: Sixty-four patients (OSMF and OSCC) were undertaken and were classified into 3 groups, OSMF patients (Group I, 34), OSCC (Group II, 30), and healthy controls (Group III, 26). Immunoturbidimetry method was used for the estimation of CRP levels. Results: Maximum cases in Group I was seen in the age group 40-60 years (males-10, females-3), Group II in the age group 40-60 years (males-11, females-5) and Group III (males-5, females-6). The mean CRP level in Group I was 6.12 ± 4.5 mg/l, in Group II was 28.4 ± 21.5 mg/l, and in Group III was 3.15 ± 2.19 mg/l. The difference was significant (P < 0.05). Conclusion: Authors found that OSMF and oral cancer patients had increased CRP levels as compared to healthy subjects.